2008
DOI: 10.1017/s026505170700770x
|View full text |Cite
|
Sign up to set email alerts
|

Students' assessments of music learning experiences from kindergarten to university

Abstract: This article reports on a retrospective study of Finnish pre-service elementary teachers' assessments of their musical experiences in nursery school and elementary and secondary school and real-time study of their experiences in teacher training. The participants (N = 590) had received musical instruction in five age groups (4–6 years, 7–12 years, 13–15 years, 16–19 years, 20–25 years). The assessments were most positive in the 4–6 years group and thereafter declined until puberty in the 13–15 years group. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…Studies have shown that girls generally hold more favourable attitudes about music class and musical experiences than boys do (Haladyna & Thomas, 1979; Vander Ark et al ., 1980; Crowther & Durkin, 1982; Eccles et al ., 1993; Phillips & Aitchison, 1998; Ruismäki & Tereska, 2008). Further, as primary students grow older, the gender gap in positive attitude towards music class has been found to widen, with boys developing increasingly negative attitudes (Nolin, 1973; Vander Ark et al ., 1980).…”
Section: Primary Schoolchildren's Preferences For Music Class Activitiesmentioning
confidence: 99%
“…Studies have shown that girls generally hold more favourable attitudes about music class and musical experiences than boys do (Haladyna & Thomas, 1979; Vander Ark et al ., 1980; Crowther & Durkin, 1982; Eccles et al ., 1993; Phillips & Aitchison, 1998; Ruismäki & Tereska, 2008). Further, as primary students grow older, the gender gap in positive attitude towards music class has been found to widen, with boys developing increasingly negative attitudes (Nolin, 1973; Vander Ark et al ., 1980).…”
Section: Primary Schoolchildren's Preferences For Music Class Activitiesmentioning
confidence: 99%
“…The intermediate level is considered a difficult time as the initial excitement of learning has often subsided (Ruismäki & Tereska 2008). Uszler et al (2000) state that the intermediate student has many other family and extra-curricular activities that can lead to a lack of time, energy and motivation for learning the piano, hence it represents 'a crucial point in the student's development' (Bastien, 1995, p. 170).…”
Section: A N O V E R V I E W O F K E Y I S S U E S R E L E V a N T T mentioning
confidence: 99%
“…The intermediate level is considered a difficult time as the initial excitement of learning has often subsided (Ruismäki & Tereska 2008). Uszler et al .…”
Section: An Overview Of Key Issues Relevant To the Intermediate Pianomentioning
confidence: 99%
See 1 more Smart Citation
“…Based on their study involving different age groups in Finland, Ruismäki and Tereska (2008) have reported that students associated the most enjoyable experience in music lessons with singing and the least enjoyable experience with leaming music theory. At the same time, the main reason for not wanting to sing in lessons was associated with not liking the teacher.…”
Section: Introductionmentioning
confidence: 99%